THE ABORTION PROBLEM SITUATION IN RUSSIA IN 2008-2015 YEARS - M. N. Bantyeva (Акушерство, гинекология и репродукция)
The urgency of the problem of abortion in Russia is determined by its medical and social significance in connection with a high prevalence, significant contribution to the performance of reproductive losses, maternal mortality and gynecological morbidity. Objective. To analyze the dynamics and structure of abortions in Russia for 2008-2015. Materials and Methods. Official statistic data (federal form №13) is analyzed by descriptive method of statistics. Results. For the period 20082015 the total number of abortions decreased by 28.7%. During the described period the number of abortion for social reasons has decreased – by 96.7%, on the second rate of decline registered illegal abortions- by 87.0%, on the third place – medical abortions, the number of which decreased by 53.8%, the number of unspecified abortions decreased by 40.5%, the number of abortion for medical reasons decreased by 9.7%. While, the number of spontaneous abortions in opposite increased by 34.6%. Conclusion. Despite the decline in the number of abortions their level remains high and is accompanied by adverse changes in their structure, in which the proportion of spontaneous abortion increased. Miscarriage in 2015 year is 12.3% of pregnancies ended by childbirth, is indicating an increase its prevalence in the population – as the main marker of damage of reproductive health of women.